Artistic self-representations and cognitive complexity in Roz Chast's Can't We Talk About Something More Pleasant?. Issue 1 (2nd January 2021) - Wang, W. Michelle
ABSTRACT: This essay elucidates how Rita Felski's critical concept of recognition —and its corresponding emphases on relationality and intersubjectivity—serves as a productive mode for examining representations of illness and the challenges associated with end-of-life care in the graphic memoir form. In Roz Chast's Can't We Talk About Something More Pleasant? (2014), not only does the cartoonist chronicle her elderly parents' struggles with escalating physical and cognitive debilitation, the graphic memoir is also an intimate record of Chast's own difficult emotional journey of re-orientating from her role as their child to their caregiver. By attending to artistic self-representations in Chast's graphic memoir, I explain how its embedding of layered subjectivities is built on a relational model of care ethics that illuminates the emotional complexities of caring for one's loved ones.